ADOPTION OF MOBILE-ASSISTED LANGUAGE LEARNING IN IMPROVING COLLEGE STUDENTS' ENGLISH LISTENING SKILLS - Cecep Hilman; Muhammad Ishom; Suhana Sarkawi; Khuloud Mustafa Alouzi (International Journal of Teaching and Learning, 2025)
The use of mobile technology and language learning applications (Mobile-Assisted Language Learning or MALL) as a tool to improve students' English listening skills effectively. MALL has been proven to increase student achievement, engagement, and participation in language learning, especially in the aspect of listening skills. With that, the adoption of MALL is a promising and effective strategy in improving college students' English listening skills, but it requires careful planning and implementation to maximize its benefits.